How can I find the explicit formula for the inverse of sinh?

Write y = sinh^(-1)(x) ie x = sinhy. Then writing this in terms of exponentials and multiplying by 2 we will get 2x = exp(y) - exp(-y). Multiply by exp(y) and rearrange to obtain exp(2y) - 2xexp(y) -1 = 0. Then this is is simply a quadratic in exp(y), so using the quadratic equation or completing the square we get exp(y) = x + sqrt(x^2 +1). Notice we take the positive square root since we must have exp(y) > 0. Then simply take logs of both sides to get the equation for y in terms of x. This is now the inverse of sinh.

Related Further Mathematics A Level answers

All answers ▸

What is the value of x from (x+2)^2=4


How to determine the modulus of a complex number?


A particle is projected from the top of a cliff, 20m above the sea level at an angle of 30 degrees above the horizontal at 20m/s. At what vertical speed does it hit the water?


a) Find the general solution to the differential equation: f(x)=y''-12y'-13y=8. b) Given that when x=0, y=0 and y'=1, find the particular solution to f(x).


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences